134k views
9 votes
2(x + 3)=x - 4
help me ​

2 Answers

2 votes

Answer:

x = -10

Explanation:

Simplify both sides of the equation.

2 (x+3) = x − 4

(2) (x) + (2) (3) = x + −4 (Distribute)

2x + 6 = x + − 4

2x + 6 = x − 4

Subtract x (1x) from both sides

2x + 6 − x = x − 4 − x

x + 6 = − 4

Subtract 6 from both sides

x + 6 − 6 = − 4 − 6

x = -10

User FabienRohrer
by
5.2k points
5 votes

Answer:

x = -10

Explanation:

2(x+3) = x-4 --> multiply (x+2) times 2

2x+6 = x - 4 --> subtract x from both sides

x+6 = -4 --> subtract 6 from both sides

x = -10

User FujiRoyale
by
5.1k points